The role of urinary 5- Hydroxyindoleacetic acid determination in diagnosis of acute appendicitis (Tikrit Journal of Pharmaceutical Sciences, 2023)
Background: Appendicitis is associated with high rate of wrong diagnosis. Objective. To evaluate the predictive value of 5-HIAA in diagnosis of appendicitis. Patients & Methods: Spot urine samples were collected from 147 patients with appendicitis and 45 healthy control. 5-HIAA was detected in urine samples in all patients using ELISA method. Results: The mean 5-HIAA level was 4.5 umol/mmol creatinine in healthy individuals, 5.8 umol/mmol creatinine in wrongly diagnosed appendicitis, and 15.7 umol/mmol creatinine in patients with appendicitis. The difference between patients group with appendicitis and other 2 groups was statistically highly significant [P